1981
DOI: 10.1159/000158342
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Metabolism of Noradrenaline by Blood Vessels of Perinephritic Hypertensive Dogs

Abstract: Tissue noradrenaline content as well as uptake and metabolism of tritiated exogenous noradrenaline were studied comparatively, in vitro in mesenteric arteries, and in saphenous veins of normotensive and perinephritic hypertensive dogs. The influence of cocaine, iproniazid and 3’-4’-dihydroxy-2-methyµ-propiophenone (U-0521) on these variables wasalso investigated. The concentration of (–)-7-3H-noradrenaline used was 1.084 µM. No changes were observed in noradrenaline content, uptake and metabolism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…The latter possi bility is supported by the finding that in iso lated blood vessels, the neuronal uptake and accumulation of NE is considerably greater in blood vessels from SHR rats than in ves sels from WKY rats [Webb et al, 1981;Whall et al, 1980], It is now well established that in a variety of stress states (including sympathetic neuronal stimulation), there is an enhanced concentration of NE in plasma from WKY rats [Roizen et al, 1975;McCarty and Kopin, 1978;Kvetnansky et al, 1979;Picotti et al, 1982], The latter findings are consistent with an enhanced releasable pool of NE in vascular sympathetic nerves. It should be noted, however, that in two other nongenetic experimental models of hyperten sion NE contents of blood vessels are gener ally decreased [Garrett et al, 1981;Crabb et al, 1980] The most significant observation from the present findings is the existence of a differ ence in tissue concentrations of a readily mea surable neurotransmitter substance in sympa thetically innervated tissues from SHR and WKY rats. Moreover, these differences are not restricted to isolated vascular beds, but are detectable in other organs and glands.…”
Section: Discussioncontrasting
confidence: 46%
“…The latter possi bility is supported by the finding that in iso lated blood vessels, the neuronal uptake and accumulation of NE is considerably greater in blood vessels from SHR rats than in ves sels from WKY rats [Webb et al, 1981;Whall et al, 1980], It is now well established that in a variety of stress states (including sympathetic neuronal stimulation), there is an enhanced concentration of NE in plasma from WKY rats [Roizen et al, 1975;McCarty and Kopin, 1978;Kvetnansky et al, 1979;Picotti et al, 1982], The latter findings are consistent with an enhanced releasable pool of NE in vascular sympathetic nerves. It should be noted, however, that in two other nongenetic experimental models of hyperten sion NE contents of blood vessels are gener ally decreased [Garrett et al, 1981;Crabb et al, 1980] The most significant observation from the present findings is the existence of a differ ence in tissue concentrations of a readily mea surable neurotransmitter substance in sympa thetically innervated tissues from SHR and WKY rats. Moreover, these differences are not restricted to isolated vascular beds, but are detectable in other organs and glands.…”
Section: Discussioncontrasting
confidence: 46%
“…Arterial hyper trophy could be the consequence of a trans mural chronic hypertension, since similar reactions of smooth muscle to an enhanced load have been described for arterial smooth muscle in chronic experimental hyperten sion [11,17,22,[25][26][27][42][43][44] and small intestine smooth muscle [19][20][21]. Further, Azevedo et al [5] and Garret et al [22] recently showed that hypertrophied mesen teric arteries taken from perinephritic hyper tensive dogs also showed degenerative adrenergic nerves accompanied by a de crease in their noradrenaline content.…”
Section: Origin O F the Artery Wall Structural Modificationsmentioning
confidence: 98%
“…8 -9 Tissue concentrations of norepinephrine are reported to be decreased in mesenteric artery and heart in renal hypertensive animals. 10 " On the other hand, the density of sympathetic innervation has been shown to increase in brain arteries of the spontaneously hypertensive rats (SHR). 5 l2 Furthermore, autoregulation of lower and higher limits of cerebral blood flow has been reported to change in hypertensive animals.…”
mentioning
confidence: 99%